RESPON TANAMAN TOMAT (Lycopersicum esculentum Mill) TERHADAP PEMBERIAN BERBAGAI JENIS MULSA DAN PUPUK NPK 16:16:16 - Liza Alvionita; Zulkifli; Selvia Sutriana (DINAMIKA PERTANIAN, 2025)
The purpose of the study was to determine the response of tomato plants to the application of various types of mulch and pearl NPK fertilizer 16:16:16, both by interaction and primarily. It was carried out at the Horticultural Seed Center on Jalan Kaharuddin Nasution, Pekanbaru City, for five months, from August to December 2020. This study used a 2-factorial Completely Randomized Design (CRD). The first factor was the type of mulch (M), with four levels: no mulch, reed mulch, rice straw mulch, and silver-black plastic mulch. The second factor was NPK Mutiara 16:16:16 (N), with four levels: 0, 3.75, 7.5, and 11.25 g/plant. Parameters observed were plant height, number of primary branches, flowering age, harvest age, number of fruits per plant, fruit weight per plant, fruit weight per fruit, and number of remaining fruits. The data were statistically analyzed, and the BNJ test was performed at the 5% level. The treatment of mulch and NPK Mutiara 16:16:16 fertilizer had a significant interaction effect on plant height, flowering age, harvest age, number of fruits per plant, fruit weight per plant, fruit weight per fruit, and number of fruit residues. The best treatment was rice straw mulch and NPK Mutiara 16:16:16 at a dose of 7.5 g/plant (M2N2). The main effect of mulch type on all parameters observed showed that rice straw mulch was the best treatment. The main effect of NPK Mutiara 16:16:16 was significant across all parameters; the best treatment was 7.5 g/plant.